Uses and gendered approaches: Dialogues around the intervention of cultural heritage - Ayala Macías, Elvia Guadalupe (2021)
This article proposes the need to reformulate the doctrinal guidelines that support heritage studies, aswell as to reposition the incidence of social phenomena in contexts of historical and cultural value, in which aparadox is generated between the conservation of the materiality of monumental assets and the significanceresulting from the new uses that are given to them, for this, we will refer specifically to the feminist socialmanifestations that have occurred in recent years in the Mexican territory. From this context, the reader is invited to review the current state of conceptualizations and heritage legislation, with the intention of considering more integrative theoretical approaches to gender and public space. This interpretative extension is based on the ethnographic review of material disseminated in digital media, with this exercise, we seek to analyze the controversial reactions that have arisen from the physical and virtual interventions made by feminist groups in heritage sites, revealing various narratives in relation to the contemporary resignification and delegitimization of heritage. It should be pointed out that this research is carried out from a multidisciplinary and intersectional point of view, inviting the reader to carry out an in-depth review of the perceptions, attitudes and values that society constructs around historical and cultural assets.